Relationship among body condition, subcutaneous fat and production performance of Jersey crossbred cows - PAUL, ABHISHEK; BHAKAT, CHAMPAK; MANDAL, DK; MANDAL, A; MOHAMMAD, A; CHATTERJEE, A; DUTTA, T K (The Indian Journal of Animal Sciences, 2019)
To determine relationship between BCS, ramp fat thickness, body measurements and milk yield, a total of 44 Jersey crossbred cows were observed from calving to 120 days post-partum. The ultrasonography images were recorded from rump region during entire experimental period. Statistically analyzed data revealed that BCS, HG, THT were significantly (P